2010
DOI: 10.1124/dmd.109.031831
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Whole Genome Gene Expression Profiles of HepaRG Cells and HepG2 Cells to Primary Human Hepatocytes and Human Liver Tissues

Abstract: ABSTRACT:HepaRG cells, derived from a female hepatocarcinoma patient, are capable of differentiating into biliary epithelial cells and hepatocytes. More importantly, differentiated HepaRG cells are able to maintain activities of many xenobiotic-metabolizing enzymes, and expression of the metabolizing enzyme genes can be induced by xenobiotics. The ability of these cells to express and induce xenobiotic-metabolizing enzymes is in stark contrast to the frequently used HepG2 cells. The previous studies have mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(192 citation statements)
references
References 24 publications
7
174
1
Order By: Relevance
“…Recently, omics technologies have entered the field of toxicology, leading to toxicogenomics, a very powerful tool for studying the toxicity of substances using cellbased assays and for deciphering chemical modes of action (Hartung 2010;Jennings et al 2013;Pisani et al 2015). In particular, the transcriptomic similarity of HepaRG to primary human hepatocytes is encouraging for the use of this model to study xenobiotic metabolism and hepatotoxicity (Hart et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, omics technologies have entered the field of toxicology, leading to toxicogenomics, a very powerful tool for studying the toxicity of substances using cellbased assays and for deciphering chemical modes of action (Hartung 2010;Jennings et al 2013;Pisani et al 2015). In particular, the transcriptomic similarity of HepaRG to primary human hepatocytes is encouraging for the use of this model to study xenobiotic metabolism and hepatotoxicity (Hart et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Olsavsky et al (2007) compared global gene expression profiles of HepG2, Huh7, human primary hepatocytes, and human liver slices. Hart et al (2010) recently compared whole-genome gene expression profiles of HepaRG cells and HepG2 cells with that of primary human hepatocytes and demonstrated that many DMETs are expressed at a level in HepaRG cells comparable to that in HepG2 cells in comparison with primary human hepatocytes. To overcome the disadvantages of a short life span and limited availability of primary human hepatocytes, immortalized "normal" human liver epithelial cell lines were established by introduction of the simian virus 40 large T antigen gene.…”
Section: Introductionmentioning
confidence: 99%
“…NC, negative control; GTSF1, gametocyte specific factor 1; si, small interfering. these changes can affect protein concentrations and the copy number (24)(25)(26). Conversely, genetic changes involved in the development of liver cancer, the cancer protein secretomes and the biological significance of human leucocyte antigen expression in HCC tumors closely resemble those of the HepG2 cells observed in previous studies (27)(28)(29).…”
Section: Discussionmentioning
confidence: 49%